Epigenetic Small Molecules Rescue Nucleocytoplasmic Transport and DNA Damage Phenotypes in C9ORF72 ALS/FTD - Melina Ramic (MDPI AG, 2021)
Amyotrophic lateral sclerosis (ALS) is a progressive and fatal neurodegenerative disease with available treatments only marginally slowing progression or improving survival. A hexanucleotide repeat expansion mutation in the C9ORF72 gene is the most commonly known genetic cause of both sporadic and familial cases of ALS and frontotemporal dementia (FTD). The C9ORF72 expansion mutation produces five dipeptide repeat proteins (DPRs), and while the mechanistic determinants of DPR-mediated neurotoxicity remain incompletely understood, evidence suggests that disruption of nucleocytoplasmic transport and increased DNA damage contributes to pathology. Therefore, characterizing these disturbances and determining the relative contribution of different DPRs is needed to facilitate the development of novel therapeutics for C9ALS/FTD. To this end, we generated a series of nucleocytoplasmic transport “biosensors”, composed of the green fluorescent protein (GFP), fused to different classes of nuclear localization signals (NLSs) and nuclear export signals (NESs). Using these biosensors in conjunction with automated microscopy, we investigated the role of the three most neurotoxic DPRs (PR, GR, and GA) on seven nuclear import and two export pathways. In addition to other DPRs, we found that PR had pronounced inhibitory effects on the classical nuclear export pathway and several nuclear import pathways. To identify compounds capable of counteracting the effects of PR on nucleocytoplasmic transport, we developed a nucleocytoplasmic transport assay and screened several commercially available compound libraries, totaling 2714 compounds. In addition to restoring nucleocytoplasmic transport efficiencies, hits from the screen also counteract the cytotoxic effects of PR. Selected hits were subsequently tested for their ability to rescue another C9ALS/FTD phenotype—persistent DNA double strand breakage. Overall, we found that DPRs disrupt multiple nucleocytoplasmic transport pathways and we identified small molecules that counteract these effects—resulting in increased viability of PR-expressing cells and decreased DNA damage markers in patient-derived motor neurons. Several HDAC inhibitors were validated as hits, supporting previous studies that show that HDAC inhibitors confer therapeutic effects in neurodegenerative models.